A high-performance ultraviolet solar-blind photodetector based on a β-Ga2O3 Schottky photodiode. Issue 44 (30th October 2019) - Liu, Zeng; Wang, Xia; Liu, Yuanyuan; Guo, Daoyou; Li, Shan; Yan, Zuyong; Tan, Chee-Keong; Li, Wanjun; Li, Peigang; Tang, Weihua
Abstract : A high-performance and easily fabricated Ni/β-Ga2 O3 Schottky photodiode was developed for ultraviolet solar-blind detection. Abstract : UV ray detection near the earth surface has become urgent due to the serious effects of UV rays on human health, the environment and the biological evolution; therefore, the development of energy-saving UV photodetectors with high responsivity, specific detectivity, and sensitivity is urgently desired. Herein, we fabricated a lateral β-Ga2 O3 Schottky photodiode on a sapphire substrate via magnetron sputtering using Ti and Ni as ohmic and Schottky contacts, respectively. The photodiode shows rectifying behaviors in the dark and under 254/365 nm UV light illuminations. As a photodetector, it exhibits the high photo-to-dark current ratio of 2.83 × 10 5 owing to its low dark current (1.32 × 10 −11 A) and strong UV absorbance. The responsivity at 250 nm could reach up to 144.46 A W −1 at 10 V. The external quantum efficiency of 64 711% and the ideal specific detectivity of 7.29 × 10 14 cm Hz 1/2 W −1 (Jones) were also achieved. The rejection ratio ( R 250 nm / R 400 nm ) was as high as 4.8 × 10 3, suggesting high wavelength selectivity. The responsivity of 2301.78 A W −1 at 180 V proves the ability of this photodetector to operate at high voltages. In addition, it can operate with the responsivity of 0.73 mA W −1 and the specific detectivity of 3.35 × 10 10 cm Hz 1/2 W −1 (Jones) at zero bias. Overall, the lateral Ti/β-Ga2 O3 /Ni structured Schottky photodiode was verified as an excellent candidate for UV solar-blind detection with high performance and low energy consumption.